2014
DOI: 10.15296/ijwhr.2014.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nitric Oxide with Minimal Stimulation on Patients with Polycystic Ovarian Syndrome

Abstract: Objectives: Infertility is one of the most prevalent problems among young couples especially in women with Polycystic Ovary Syndrome. In women, PCO is associated with lack of ovulation, abdominal obesity and insulin resistance. The aim of this study is to investigate the effect of nitric oxide with minimal stimulation in the treatment of infertility in women with PCOS. Materials and Methods: In a randomized single blind clinical trial (RCT), 120 women who had polycystic ovarian syndrome (PCOS), were with PCOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Morphine, a pure alkaloid isolated from opium,[ 1 ] can relieve pain[ 2 ] and has a wide clinical application. Studies have shown that morphine can induce ovarian cysts[ 3 ] and alter lipid metabolism. [ 4 ] Gamma-aminobutyric acid (GABA), which is known as the main inhibitory neurotransmitter, is involved in preventing the development of ovarian cysts.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine, a pure alkaloid isolated from opium,[ 1 ] can relieve pain[ 2 ] and has a wide clinical application. Studies have shown that morphine can induce ovarian cysts[ 3 ] and alter lipid metabolism. [ 4 ] Gamma-aminobutyric acid (GABA), which is known as the main inhibitory neurotransmitter, is involved in preventing the development of ovarian cysts.…”
Section: Introductionmentioning
confidence: 99%